Migrasi Bugis dan Madura di Selatan Papua Barat: Perjumpaan Etnis dan Agama di Minoritas Muslim - Ismail Suardi Wekke (Wakil Rektor III Bidang Kemahasiswaan dan Kerjasama, 2017)
Bugis and Madura already reach eastern part of Nusantara since 15th century. Both Indonesian ethnic have migration tradition as the common identity. With traditional transportation, they explore Makassar to Banda, and from Sampang to Surabaya. This research was conducted for six months. It was extended to three months. Therefore, research duration was nine months. Observation and in-depth interview were conducted to collect data. This research was conducted in Eastern part of Indonesia. Papua Island, Maluku, and surrounding islands those locate from capital city. It is known small island, big issues of criminality and others notorious issues. On the other hand, it is a peaceful area and multicultural society. Bugis and Madura among reside on those islands. They mainly concerned with fishing, business, and maritime activities. The notion of social interaction in economic activities sees cooperation and recognition. This research also argues that religious interaction and collective life emerge between Bugis and Madura and other ethnics. They construct new identity as Papua Bugis and social harmony Madura of Java. They establish migration on the basis of economic and social interest. Furthermore, this article concludes that they participate and construct as citizens in the society at large.